المرجعية في الفكر الغربي المعاصر وتجلياتها التربوية: The Frame of Reference in Contemporary Western thought and its Educational Manifestations - ملكاوي فتحي حسن (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2019)
Most of today's Muslim societies derive their educational ideas, concepts and practices from the contemporary Western experience, which calls for our understanding of the frame of reference of the prevailing educational thought in the West with full awareness, responsibility and objectivity. This would hopefully help us to develop proper approaches to deal and interact and systems and specific features of Western Educational Thought, and have needed awareness of the implications of borrowing from it in our educational policies and plans, and the problems it poses to educational reform efforts in our Muslim contemporary societies. It is our hope that we will develop clear understanding of the Supreme Islamic frame of reference in the educational reform that would contribute to the reconstruction of Islamic character, Islamic societies and Islamic Ummah to achieve what Allah Almighty has entrusted on Mankind in building civilization on the light of the Divine Revelation and the Prophetic Guidance and to help Muslims to have an active presence in the world arena with positive contribution.